5d, a novel analogue of 3-n-butylphthalide, protects brains against nervous injury induced by ischemia/reperfusion through Akt/Nrf2/NOX4 signaling pathway1. Issue 85 (16th September 2015) - Ling, Jingjing; Ji, Hui; Wang, Xiaoli; Zhang, Yihua; Zhang, Chao; Song, Huizhu; Li, Jing; Zhao, Min; Ping, Fengfeng; Qian, Jun
<x xml:space="preserve">Abstract</x> 5d, a novel analogue of 3-n-butylphthalide, decreases NADPH oxidase activity by the activation of Nrf2 through PI3K/Akt signaling pathway after I/R and may be an effective candidate for the treatment of ischemic stroke.